2020
DOI: 10.1109/access.2020.2971604
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Fraud Detection Metrics in Business Processes

Abstract: Fraud is a primary source of organization losses, amounting to up to 5% of yearly revenues. Process-based fraud (PBF) is fraud involving a deviation from the standard operating procedure (SOP) of business processes. PBF hinders the achievement of business objectives because business processes operationalize organizational strategies. A systematic content analysis of the literature was conducted on fraud detection metrics in business processes. The current state of fraud detection was surveyed by focusing on PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…The research findings showed that, a great portion of research had examined detection metrics for possible fraud, but less attention had been paid to Process-Based Fraud (PBF). Also, the already available PBF detection metrics did not sufficiently address the needs of separate conceptual perspectives on firm processes (Omair and Alturki, 2020). Aslan and Kızıl's study (2019) titled "Üretim Maliyetlerinin Denetimine Genel Bir Bakış" stressed that, audit is a very important and critical for businesses in today's business world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research findings showed that, a great portion of research had examined detection metrics for possible fraud, but less attention had been paid to Process-Based Fraud (PBF). Also, the already available PBF detection metrics did not sufficiently address the needs of separate conceptual perspectives on firm processes (Omair and Alturki, 2020). Aslan and Kızıl's study (2019) titled "Üretim Maliyetlerinin Denetimine Genel Bir Bakış" stressed that, audit is a very important and critical for businesses in today's business world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the literature review on PBF detection metrics 4 are summarized in Fig. 4 in the form of a literature map [11]. The literature map illustrates the topics relevant to fraud detection metrics in business processes, as well as the frequency of their recurrence in the literature.…”
Section: Process Perspectivementioning
confidence: 99%
“…The literature map illustrates the topics relevant to fraud detection metrics in business processes, as well as the frequency of their recurrence in the literature. Omair and Alturki [11] demonstrated that, at present, the explicitly defined PBF detection metrics, which are listed in Table Ⅰ, do not adequately address the essential conceptual perspectives of business process.…”
Section: Process Perspectivementioning
confidence: 99%
See 2 more Smart Citations